Motivative aspect of professional self-development of the future modern teacher of physical culture. - Курнишев, Юрій; Мосейчук, Юрій; Турченяк, Станіслава (Інноваційна педагогіка: науковий журнал Причорноморського науково-дослідного інституту економіки та інновацій, 2022)
The article identifies the dependence of the effectiveness of motivation on the ability of the teacher to form the student's need to achieve the goal, stimulate him to action, the level of creative interaction in the system "teacher-student". It is proved that the main levers of motivation for self-development are incentives as an external motivation for action. The author of the article describes stimulation as the unity of purpose, content, forms, methods, techniques, means of activity of the leader and other subjects, according to psychological, age, gender features, individual style of activity, experience. In the process of professional training, the future specialist must gain experience of consistent purposeful self-knowledge and personal growth. Only a person with a clear self-awareness is able to assess own individuality, actualize the inner creative potential, become a subject of selfdevelopment. The necessity to study a motivation is caused by the fact it is one of the methods of personality control, influence on the needs and desires. Last time, the positive changes occur in the educational system and they allow a teacher to realize own creative potential, be an active participant of innovative processes. In this context, the target of a teacher is to use a motivation as a process of encouraging a student to the achievement as personal purposes and the purposes of students too. Accordingly, it is important to research a state of motivation and the existence of some incentives of teachers of the secondary school. The concept of personality as a subject of creative activity implies the value attitude of a person to self-development and self-realization and gives us the opportunity to talk about the individual as a subject of self-development. Personality development in the process of professional training is an active creative process carried out by the student in cooperation (partnership) with the teacher, one of the results of which is the individual's ability to self-actualization, ability to find new meanings in a particular case and throughout the life.
Keywords: teacher of physical culture; culture of pedagogical communication; motivation, need; self-development; incentives